Memory and multitasking performance during acute allergic inflammation in seasonal allergic rhinitis. Issue 4 (27th February 2017) - Trikojat, K.; Buske‐Kirschbaum, A.; Plessow, F.; Schmitt, J.; Fischer, R.
Summary: Background: In previous research, patients with seasonal allergic rhinitis (SAR) showed poorer school and work performance during periods of acute allergic inflammation, supporting the idea of an impact of SAR on cognitive functions. However, the specific cognitive domains particularly vulnerable to inflammatory processes are unclear. Objective: In this study, the influence of SAR on memory and multitasking performance, as two potentially vulnerable cognitive domains essential in everyday life functioning, was investigated in patients with SAR. Methods: Non‐medicated patients with SAR ( n = 41) and healthy non‐allergic controls ( n = 42) performed a dual‐task paradigm and a verbal learning and memory test during and out of symptomatic allergy periods (pollen vs. non‐pollen season). Disease‐related factors (e.g. symptom severity, duration of symptoms, duration of disease) and allergy‐related quality of life were evaluated as potential influences of cognitive performance. Results: During the symptomatic allergy period, patients showed (1) poorer performance in word list‐based learning ( P = 0.028) and (2) a general slowing in processing speed ( P < 0.001) and a shift in processing strategy ( P < 0.001) in multitasking. Yet, typical parameters indicating specific multitasking costs were not affected. A significant negative association was found between learning performance and duration of disease ( r = −0.451, P = 0.004), whereas symptom severity ( r = 0.326; P = 0.037) and quality of life ( r = 0.379; P = 0.015) were positively associated with multitasking strategy. Conclusions: Our findings suggest that SAR has a differentiated and complex impact on cognitive functions, which should be considered in the management of SAR symptoms. They also call attention to the importance of selecting sensitive measures and carefully interpreting cognitive outcomes.